1975
DOI: 10.1136/jnnp.38.8.805
|View full text |Cite
|
Sign up to set email alerts
|

Regional curare for the reduction of the safety factor in human motor end-plates studied with single fibre electromyography.

Abstract: SYNOPSIS A method employing six minutes of regional curarization with 0.5 mg D-tubocurarine and single fibre electromyographic measurements (SFEMG) was used in order to study the effect of an additional small dose of D-tubocurarine. The effect of the additional dose was most pronounced in terms of increased jitter, on motor end-plates with the initially highest jitter. The combination of regional curarization and SFEMG jitter recordings offers a sensitive technique for detecting mild effects of various drugs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This generally is attributed to the increase in the drug response sensitivity of endplates with a low safety factor. 17 This attribution may be valid as the drug affects only the postsynaptic membrane; but, this phenomenon also is well explained by the alternative suggested here. The sensitivity of low-safety factor end-plates to curare need not necessarily increase to explain the linear correlation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This generally is attributed to the increase in the drug response sensitivity of endplates with a low safety factor. 17 This attribution may be valid as the drug affects only the postsynaptic membrane; but, this phenomenon also is well explained by the alternative suggested here. The sensitivity of low-safety factor end-plates to curare need not necessarily increase to explain the linear correlation.…”
Section: Discussionmentioning
confidence: 84%
“…17,22 Furthermore, variations in MCD values (⌬MCD) are linearly correlated with the initial jitter. This generally is attributed to the increase in the drug response sensitivity of endplates with a low safety factor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies in humans have found that after injection of a given dose of curare those motor endplates with the highest initial jitter showed the greatest increase in MCD values. 24 In Lewis rats, jitters progressively decreased with age, suggesting that neuromuscular transmission is facilitated in aged Lewis rats. Aged female BN rats, however, showed signs of disturbed neuromuscular transmission before immunization.…”
Section: Discussionmentioning
confidence: 98%
“…SFEMG assesses neuromuscular junction (NMJ) failure by recording complete failure of myofiber depolarization (blocking) or reduction in efficiency of NMJ transmission measured by an increase in MCD. 11,13,14 Fiber density (FD), measured as the number of unique muscle-fiber action potentials recorded within the active area of the SFEMG electrode, provides an estimate of the packing density of muscle fibers. Increased FD is observed in neurogenic or myopathic diseases that disrupt motor unit organization through denervation and reinnervation, fiber splitting, or changes in muscle fiber diameter.…”
mentioning
confidence: 99%